Effect of COVID-19 lockdown on injury incidence and burden in amateur rugby union - Tondelli, Eduardo (2023)
Fil: Tondelli, Eduardo. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas; Argentina